ASSESSMENT OF COGNITIVE DYSFUNCTION IN THE MILITARY WITH ALCOHOL-INDUCED MENTAL AND BEHAVIORAL DISORDERS WITH DEPRESSION COMORBIDITY - Fitkalo О.S.; Lyzak, O.L.; Neurova, A.B. (World of Medicine and Biology, 2020)
The article presents the results of a psychodiagnostic study aimed to identify cognitive impairment and comorbid depressive states in the military with alcohol-induced mental and behavioral disorders. Up to 50 % of borderline cognitive disorders were found in patients of both groups (N = 85). Depressive symptoms were found in 100 % of patients in the experimental group; 95.21 % demonstrated anxiety symptoms. Depression has been shown to correlate with cognitive impairment in patients with alcohol-induced mental and behavioral disorders. To reduce cognitive impairment, the patients of both groups were administered Cytoflavin metabolic drug in combination with traditional treatment. Following the course of treatment with addition of Cytoflavin, in 68 (80 %) patients of both groups there was a decrease in the cognitive dysfunction symptoms, normalization of sleep, and improvement of mood, which affected the quality of life in patients of both groups.